2023
DOI: 10.1101/2023.04.20.537611
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nfe2l1-mediated proteasome function controls muscle energy metabolism in obesity

Abstract: Muscle function is an important denominator of energy balance and metabolic health. Adapting the proteome to energetic challenges, in response to diet or fasting, is facilitated by programs of proteostasis, but the adaptive role of the ubiquitin-proteasome system (UPS) in muscle remains unclear. Here, using a multi-omics approach, we uncover that the distinct metabolic condition of obesity is associated with recalibration of the UPS in muscle. Interestingly, obesity is associated with the activation of the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…Loss of NFE2L1 in mice is associated with weaker muscles and lower physical capacity. Curiously, they display an enhanced energy metabolism and are more protected against highfat diet-induced obesity (Lemmer et al, 2023). We also observed that, in response to exercise, NFE2L1 is crucial for skeletal muscle recovery.…”
Section: Main Results (And Curious Findings)supporting
confidence: 53%
See 1 more Smart Citation
“…Loss of NFE2L1 in mice is associated with weaker muscles and lower physical capacity. Curiously, they display an enhanced energy metabolism and are more protected against highfat diet-induced obesity (Lemmer et al, 2023). We also observed that, in response to exercise, NFE2L1 is crucial for skeletal muscle recovery.…”
Section: Main Results (And Curious Findings)supporting
confidence: 53%
“…During the ERC PROTEOFIT project, our research has demonstrated that NFE2L1 plays a pivotal role as a regulator of proteasome genes in isolated muscle cells and transgenic mouse models (Lemmer et al, 2023). In a controlled cell culture environment designed for studying metabolism in a more isolated context, the absence of NFE2L1 results in the accumulation of ubiquitinated proteins (referred to as protein waste) due to impaired degradation by the proteasome.…”
Section: Main Results (And Curious Findings)mentioning
confidence: 99%